The Tradition of Kundangan in the Last Ten Days of Ramadan: A Study of Living Hadith in Dasin Tuban Village through the Lens of Karl Mannheim's Sociology of Knowledge. - Fuaddin, Achmad; Hadi, Ahmad Nurul (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
The tradition of Kundangan or Kenduri is one of the Indonesian Muslim practices that some groups consider Bid'ah (innovation) because it is not directly based on the Hadith of the Prophet. Research on Kenduri is generally divided into two categories: studies that assess the legality of Kenduri based on Islamic values and studies that examine the values embedded within the practice. However, research on the community's reception and the essence of Kundangan in the context of Living Hadith remains limited. This study focuses on the examination of Living Hadith related to Kundangan during the last ten days of Ramadan as practiced by the community of Dasin Village, Tambakboyo Subdistrict, Tuban Regency, using Karl Mannheim's sociology of knowledge approach. This research employs a qualitative method with a case study approach to understand this phenomenon holistically. The findings indicate that the objective meaning of the Kundangan tradition during the last ten days of Ramadan is a heritage from ancestors that involves rituals, such as reading the Qur'an, praying, and giving food parcels to guests. The expressive meanings of the Kundangan tradition vary, including views of it as ancestral heritage, the belief that ancestral spirits are present in the home and should be sent the rewards of charity, anticipation of the Night of Qadr, and efforts to maintain social relationships. The documentary meaning of the Kundangan tradition reflects an acculturation between Javanese cultural beliefs and the values of Hadith. These findings show that the Kundangan tradition is a method used by Kiai (Islamic scholars) to implement Hadith values, blending them with the local culture.